IPS Empress Onlays Luted with Two Dual-Cured Resin Cements for Endodontically Treated Teeth: A 3-year Clinical Evaluation - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2011)
The aim of this study was to evaluate the performance of IFS Empress ceramic onlays luted with two dual-cured adhesive resin cements for endodontically treated teeth. Twenty molar teeth were restored with all-ceramic restorations luted randomly with Maxcem or Clearfil Esthetic Cement & DC Bond Kit luting systems (n = 10 each) in 20 patients. The restorations were assessed using modified US Public Health Service criteria at baseline, 6 months, and 1, 2, and 3 years. A statistically significant deterioration was found for the criteria marginal integrity, anatomical form, and surface roughness. For luting of ceramic onlays, no difference between the two luting systems was detected. Int J Prosthodont 2011;24:40-42.